Representasi Diskriminasi Perbedaan Ras dalam Film Green Book: (Analisis Semiotika Charles Sanders Pierce) - Ratri Pramudita; Arief Hidayatullah; Junaidin Junaidin (Yayasan Literasi Sains Indonesia, 2025)
This study examines racial discrimination representation in the 2018 film